STRATEGIC CAPABILITIES AND EXPORT PERFORMANCE OF MANUFACTURING SME IN MALAYSIA - Siti Normah Awang Tuah; Noor Hazlina Ahmad; Hasliza Abd Halim (International Journal of Accounting, Finance and Business, 2021)
Research on export performance among SMEs in Malaysia has become more significant nowadays as export is a major source of income for most countries. It is important for SMEs especially those in emerging countries like Malaysia to look into and put their efforts to strategize their capabilities to respond to the global competition and business opportunities in enhancing their export performance. Thus, this study was conducted to examine the current SMEs capabilities before they adopt the best strategic approach to face challenge situations at hand to enhance their export performance. A quantitative approach was employed in this study and a total of 187 responses from manufacturing SME exporters were received and further analysed using Partial Least Square (PLS) technique. The results demonstrated that some strategic capabilities give significant impact but some are not towards the export performance in Malaysia.